Determining the amplitude-frequency characteristics of an electric train car floor - Holovashchenko, Oleh; Shostak, Yaroslav; Tkachenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of vibration propagation through the floor of a passenger railroad car from the base to passenger seats. The problem addressed relates to the influence of the structure of an electric train car floor on its anti-vibration properties, in particular the role of rubber shock absorbers in the process of damping floor vibrations. A mathematical model of the vibration propagation chain from the base of the car to the top layer of the floor was built. As a source of vibrations in the mathematical model, the kinematic disturbance of the base of the car was used. Two variants of the floor structure were studied – with five layers and with seven layers. The parameters of the floor layers obtained experimentally by the method of free oscillations were used in the calculations. Based on the application of specific parameters of the floor layers, a transition was performed from distributed mass, elastic, and dissipative parameters to concentrated ones. The solution to the system of differential equations of oscillations was obtained in the form of time functions of displacements and velocities of floor elements. Layer-by-layer amplitude-frequency characteristics (AFR) of the floor were constructed. Zones of resonant frequencies of the oscillating system of the car floor have been determined. The dependence of the influence of the degree of passenger loading on the resonance frequency of floor surface oscillations was established. When the load changes from minimum to maximum, the resonant frequency decreases from 15–22 Hz to 8–12 Hz. It has been confirmed that the influence of parameters of the layer of rubber shock absorbers on the floor AFR is decisive for its vibration protection. When comparing the two floor variants under consideration, there were no advantages of a seven-layer floor over a five-layer floor. AFR for the first and second layers of plywood flooring are identical. Based on the data on "dangerous" vibration frequencies for humans, the preferred value for the shock absorber installation diagram was derived – 5–6 units/m2, which could prove useful under the conditions of modernization of suburban electric train cars